Characteristics of the Leadership of the Prophet Muhammad SAW - Dinda Azzahra; Imam Mars Miasya Ibnu Ivan; Yusutria (al-Afkar, Journal For Islamic Studies, 2024)
Basically, developing countries are influenced by leaders who are able to change the social, economic, cultural and educational conditions of society. Leadership is the most important position in management, Islam has a role model in leadership, namely Nabiyullah Muhammad SAW, a leader sent by Allah SWT whose exemplary attitude and leadership model is a benchmark that can be applied in every era, successfully making the Prophet Muhammad a leader. the best in the world. The Prophet's leadership is very important to explore and explore to be used as an exemplary reference in leadership education in order to create good future leaders through the example of the Prophet Muhammad SAW. Examining the science of the habits, life journey and teachings of the Prophet Muhammad is a very extraordinary science. The glory of the role model of the Prophet Muhammad is broad and covers all aspects of life so that it is endlessly studied continuously. (Rahayuning Tyas, 2019a) The focus of this writing provides descriptions from various sources regarding 1.) Leadership of the Prophet Muhammad SAW 2.) Opinions of Orientalists towards the Prophet Muhammad SAW 3.) Keys to the Success of the Leadership of the Prophet Muhammad SAW 4.) Characteristics of the leadership of the Prophet Muhammad.